The Importance of Legitimacy - Akerlof, Robert (Published by Oxford University Press on behalf of the World Bank, 2019)
Within organizations, there are typically limits to leaders’ legitimacy. This article explores how organizations are structured in the face of such constraints. The concept of legitimacy is formalized in the context of a single-agent moral hazard model. The principal can give the agent monetary incentives; in addition, he can give the agent an order. The agent finds it costly to disobey orders provided they are legitimate. The authors find that it may be optimal for the principal to take costly actions to bolster legitimacy. The authors argue that many organizational phenomena can be understood as attempts to bolster legitimacy. Examples include: rejection of overqualified workers, bureaucracy, merger decisions, and above-market-clearing wages.